1979
DOI: 10.1073/pnas.76.2.991
|View full text |Cite
|
Sign up to set email alerts
|

Action of black widow spider venom on quantized release of acetylcholine at the frog neuromuscular junction: dependence upon external Mg2+.

Abstract: Black widow spider (Latrodectus tredecimguttatus) venom (BWSV) increases several hundredfold the frequency of occurrence of miniature end-plate potentials (Fmepp) at frog neuromuscular junctions bathed in Ringer's solutions containing either Ca2+ or Mg2t, but it has little effect on Fmepp at junctions bathed in modified Ringer's solution containing 1-2 mM ethylene glycol bis (,B-aminoethyl ether) N,N'-tetraacetic acid (EGTA) Black widow spider (Latradectus tredecimguttatus) venom (BWSV) causes a massive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 20 publications
1
59
0
Order By: Relevance
“…Like Mg2+, Co2+ and Mn2+ can support quantal release in the presence of black widow spider venom (Gorio & Mauro, 1979;Misler & Hurlbut, 1979). Also, Kita & van der Kloot (1973) found that in the absence of Ca2+, Co2+ enhanced resting, K+-stimulated, and post-tetanic m.e.p.p.…”
Section: Possible Mechanisms For Deviations From Fourth Power In Mg2+mentioning
confidence: 97%
See 1 more Smart Citation
“…Like Mg2+, Co2+ and Mn2+ can support quantal release in the presence of black widow spider venom (Gorio & Mauro, 1979;Misler & Hurlbut, 1979). Also, Kita & van der Kloot (1973) found that in the absence of Ca2+, Co2+ enhanced resting, K+-stimulated, and post-tetanic m.e.p.p.…”
Section: Possible Mechanisms For Deviations From Fourth Power In Mg2+mentioning
confidence: 97%
“…Here the measured deviations averaged 460% (range 46-1600 % for five junctions), while the predicted mean deviation for the same data was only 43 % (range 32-59 %). Thus it seems that Mg2+, which probably enters the stimulated nerve terminal (Baker & Crawford, 1972) (Blioch et al 1968;Hurlbut et al 1971), and Mg2+ can substitute for Ca2+ in supporting the massive quantal release seen in neuromuscular preparations treated with black widow spider venom (Ornberg, 1977;Gorio & Mauro, 1979;Misler & Hurlbut, 1979). Additional evidence for Mg2+-dependent release is reviewed in van der Kloot (1978).…”
Section: Possible Mechanisms For Deviations From Fourth Power In Mg2+mentioning
confidence: 99%
“…This solution was renewed once or twice during 10 min, then BWSV (0 5 glands from Italian spiders or 1 gland from American spiders) or a-LTX (0 5-1 ag) was added to the chamber, the bath gently stirred and the preparation incubated for 25-35 min. Quantal secretion is not stimulated under this condition (Misler & Hurlbut, 1979;Misler & Falke, 1987), and the toxin can be allowed to penetrate the muscle completely and bind to its receptor (Valtorta, Madeddu, Meldolesi & Ceccarelli, 1984). A wellsynchronized discharge of quanta from the various junctions in the muscle was started by applying Mg2+ and stopped by withdrawing it, and the rate of discharge was regulated by controlling the Mg2+ concentration (Misler & Hurlbut, 1979;Misler & Falke, 1987) or the temperature .…”
Section: Methodsmentioning
confidence: 99%
“…Since black widow spider venom and a-LTx probably increase the permeability of nerve terminals to monovalent and divalent cations (Finkelstein, Rubin & Tzeng, 1976;Misler & Hurlbut, 1979;Nicholls, Rugalo, Scott & Meldolesi, 1982;Fritz & Mauro, 1982;Meldolesi, Scheer, Madeddu & Wanke, 1986;Misler & Falke, 1987), all these effects of extracellular Mg2+ may result from its entry into the axoplasm. The first effect might result from interactions between increased levels of Mg2" and the cytoskeleton, and the second from the ability of high concentrations of Mg2+ to stabilize clathrin coats (Woodward & Roth, 1979) and to uncouple the clathrin 'uncoating ATPase' (Braell, Schlossman, Schmid & Rothman, 1984 …”
Section: Electrophysiologymentioning
confidence: 99%